Development of novel cancer chemopreventive agents in Europe - neglected Cinderella or rising phoenix?: a critical commentary. ESF Workshop on Cancer Chemoprevention, DKFZ, Heidelberg, September 18-20, 2005 - Gerhäuser, Clarissa; Bartsch, Helmut; Crowell, James; Flora, Silvio De; D’Incalci, Maurizio; Dittrich, Christian; Frank, Norbert; Mihich, Enrico; Steffen, Christian; Tortora, Giampaolo; Gescher, Andreas (European journal of cancer, 2006)
Abstract Agents that prevent cancer, delay its onset, or revert premalignant conditions could have dramatic beneficial impacts on human health. Although there is an urgent need to develop cancer chemopreventive agents, researchers in the field suspect that this area of scientific endeavour in Europe leads a Cinderella existence, both in terms of perception of importance and research funding. In order to review current activities in this prevention field and to seek a consensus position, an exploratory workshop was held in September 2005 at the German Cancer Research Center (DKFZ) in Heidelberg, Germany, sponsored mainly by the European Science Foundation (ESF), and also supported by the European Association for Cancer Research (EACR) and the German Cancer Society (DKG). The 35 experts from European countries and the United States of America assessed state-of-the-art cancer chemoprevention research in Europe. The aims that the workshop organizers had pre-defined were: i) assessment of the usefulness of animal models for agent identification; ii) review of ongoing preclinical and clinical work on novel agents; iii) discussion of potential biomarkers predictive for cancer preventive efficacy; and finally iv) the potential role that European pharmaceutical industries could play in furthering chemopreventive agent development. Overall the workshop aimed at raising awareness among European clinical and laboratory researchers of the importance of the development of novel, efficacious and safe cancer preventive agents.
Gesehen am 23.11.2020